Adults who were born preterm with a very low birth weight reported a similar health‐related quality of life to their term‐born peers. (8th December 2017) - Björkqvist, Johan; Hovi, Petteri; Pesonen, Anu‐Katriina; Räikkönen, Katri; Heinonen, Kati; Järvenpää, Anna‐Liisa; Eriksson, Johan G.; Andersson, Sture; Kajantie, Eero
Abstract :